Macroprocess 05 Legal Advisory - Organizational Design Division (Carlos Figueroa Picado, 2020)
The Manual 05 Legal Advisory Macroprocess aims to "To guarantee effective and timely legal advice, in domestic, international and diplomatic law to Headquarters and the Delegations". Scope: Hemispheric level. Technical-regulatory and operative actions. Centralization at strategic levels and at Headquarters. Coordination at the level of Delegations. Decentralization at operational level by country.